Adolescência e vulnerabilidade em tempos de pandemia: uma escuta psicanalítica - Schröpfer, Laís Caroline (2023)
Adolescence is a period marked by transformations and constitutes itself as a structuring psychic operation, a passage that relies on specific internal and external conditions. During this journey, the adolescent embarks on a quest to find alternative meanings of themselves, supported by elements offered by culture and their social environment, which will assist them in constructing a new psychic space, a new identity, and a re-inscription in the social bond. Thus, the presence of an inseparable connection between the social bond and this psychic operation is highlighted. This leads to questioning how social bonds in vulnerable territories unfolded amidst the covid-19 pandemic and how they resonated in the subjectivity of adolescents. Therefore, this work sought to analyze, through listening and the psychoanalytic framework, how the passage through adolescence unfolded amidst vulnerabilities during the covid-19 pandemic, understanding that this period further accentuated the inequalities that adolescents in critical social situations were already experiencing. To achieve this, we were inspired by the methodology of territorial listening, which aims to comprehend how scenarios of neglect and social exclusion impact subject formation. We conducted interviews on the streets of a socially vulnerable neighborhood in the city of Santa Maria, Rio Grande do Sul. Adolescents aged 12 to 18, family members, local residents, and individuals working in institutions that had contact with the youth were interviewed. The tools used included a semi-structured interview and an experiential diary, a recording and investigative tool where the researcher records their impressions of the listening and transference, as a means of capturing both conscious and unconscious aspects that emerge during the research. The results indicated that subjects were exposed to traumatic dimensions, neglect, and silencing during the pandemic, which impacted the processes of adolescence in these contexts. Considering that research and intervention in psychoanalysis are inseparable, a clinical tool was developed during the process, operating in the social context, specifically a sports court where football played a significant role. Within that symbolic space that engaged the discourse of adolescents, conflicts and desires emerged, and the tool became a place of socialization, recognition, and protection. Therefore, the tool demonstrated itself as a potent space for processing the youths' anxieties arising from the violence and vulnerabilities of the territory, as well as from adolescence itself. Lastly, we emphasize the importance of investing in spaces frequented by adolescents through listening, support, and identification of potentials, both in the adolescents themselves and in the territories they inhabit. This involves offering ethical-political interventions in response to the distress present in critical social situations.